Extreme weather and climate events in China under changing climate - Zhao, Weijie (Natl Sci Rev, 2020)
In the summer of 2003, a heat wave swept Europe and caused more than 70 000 additional fatalities [J.-M. Robine et al., C. R. Biologies331 (2008)]. Global warming and climate change is no longer a prophecy to be fulfilled, as strong heat waves and typhoons, as well as severe rainfalls, are becoming more severe. Extreme weather and climate events in the world, especially over Europe and North America, are widely studied and frequently reported in the media. These events may be related to the ongoing climate change. In this NSR forum, active researchers specialized in this field gather to discuss the climate and weather changes in China. They present the current changes, identify knowledge gaps, discuss the research difficulties, and propose ways forward to better serve the society with climate science. [Image: see text] Ying Sun Professor at the National Climate Center of the China Meteorological Administration, China [Image: see text] Qiuhong Tang Professor at the Institute of Geographic Sciences and Natural Resources Research of the Chinese Academy of Sciences, China [Image: see text] Zhongwei Yan Professor at the Institute of Atmospheric Physics of the Chinese Academy of Sciences, China [Image: see text] Jing Yang Professor at the Academy of Disaster Reduction and Emergency Management, faculty of Geographic Science of Beijing Normal University, China [Image: see text] Panmao Zhai Professor at the Chinese Academy of Meteorological Sciences of the China Meteorological Administration, and the current Co-Chair of the IPCC Working Group I, China [Image: see text] Tianjun Zhou Professor at the Institute of Atmospheric Physics of the Chinese Academy of Sciences, China [Image: see text] Deliang Chen (Chair) Professor at the University of Gothenburg, NSR Editorial Board member, Sweden